Preliminary use of cerebral enthropy as evaluating indicator of degree of self-adaptation in athletes - Cui, Y.-L.; Zhang, X.-R.; Wang, P. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The objective of this study is to learn more about the level of self-adaptation to the exercise load in athletes by monitoring the cerebral entropy in athletes, using the latest achievements in neuroelectrophysiology and system science to test and analyze the value of the cerebral entropy in athletes, through comparison of the value of the cerebral entropy in athletes in different events at different levels, in combination with a contrastive analysis of training levels and sports results, etc., to achieve the goal of quantitative control of sports training.